Effectiveness of Road Safety Education in Reducing Teenage Traffic Accidents: A Systematic Review - Walugembe, Francis; Le, Cua Ngoc; Nguyen, Hien Thi; Chaiwong, Sanhawat (Journal of Posthumanism, 2025)
Background: This systematic review examined the impact of road safety education (RSE) on lowering teenage traffic accidents and injuries in Southeast Asia based on existing literature. We evaluated the effectiveness of road safety education programs, contextual and cultural adaptations, the integration of practical training, implementation challenges, and the long-term impacts on changing teenage behaviour. Material and Methods: The study followed the guidelines of Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). This involved counting the number of studies showing a positive, negative, or no effect. A search of the articles in the electronic databases of PubMed, Scopus, and Google Scholar was conducted. The effectiveness of RSE was assessed by vote counting, tallying the number of studies showing positive, neutral, or negative impacts on teenage driving behaviour aged 13-19 years. A total of seventeen studies were selected for inclusion using predefined criteria. Results: Upon conducting a systematic review, 17 key studies were identified for inclusion, reflecting diverse methodologies and focus areas. Across the research, it is evident that teenagers benefit significantly from receiving both theoretical knowledge and practical training. This comprehensive approach enhances their confidence and skills in adhering to traffic safety laws. Moreover, the involvement of parents and communities emerges as a vital factor for the success of educational initiatives. Conclusion: The study emphasizes the paramount importance of prioritizing long-term behavioural change and sustainability in road safety initiatives, particularly focusing on teenagers. It advocates for a comprehensive approach involving community and parental engagement alongside educational programs. The findings emphasize the necessity for policymakers in Southeast Asia to allocate funding towards culturally sensitive and standardized RSE programs, integrating practical training and long-term reinforcement strategies.